Tranfromasi Tata Kelola Dana Pendidikan Berbasis Digital: Peluang, Risiko, Dan Strategi Penguatan Transparansi Di Indonesia - Supriyadi, M. Yusup; As Zahro, Masithoh Afifah Nuraini; Yozaga, Buana Tirta; Adianingsih, Putri; Harsono, Harsono; Indri, Indri (Universitas Pakuan, 2026)
DIGITAL-BASED EDUCATION FUND GOVERNANCE TRANSFORMATION: OPPORTUNITIES, RISKS, AND STRATEGIES FOR STRENGTHENING TRANSPARENCY IN INDONESIA This study aims to examine the opportunities and challenges of transparency in the management of digital-based education funds in Indonesia and compare them with international practices in order to formulate innovative policy recommendations. The method used is a descriptive qualitative approach through targeted literature studies and case studies using secondary data in the form of articles and journals indexed by Google Scholar for the period 2020-2025, BOS Fund regulations, and ARKAS system implementation documents and the SIPLah procurement platform. The analysis was conducted in terms of content and comparatively to identify digital mechanisms that promote transparency and factors that hinder its effectiveness. The results show that the digitization of education fund management increases procedural transparency through the standardization of planning and reporting, the traceability of transactions and procurement, and the ease of auditing and monitoring across actors, which has an impact on increasing accountability and reducing non-procedural spending practices at the school level. However, public transparency is not yet fully optimal due to differences in human resource capacity, digital literacy, and infrastructure quality, as well as the emergence of data manipulation risks at the input stage and information security issues. A comparison with international practices shows that e-procurement and contract transparency effectively increase accountability when supported by strong governance, while blockchain technology.